The N-formyl peptide receptors: much more than chemoattractant receptors. Relevance in health and disease - Napolitano, Filomena; Montuori, Nunzia (Frontiers in Immunology, 2025)
Pattern Recognition Receptors (PRRs) are a superfamily of receptors that detect molecular structures typical for pathogens and damaged cells and play a crucial role in the proper function of the innate immune system. A particular subgroup of membrane-bound PRRs is represented by the N-formyl peptide receptors (FPRs) that consist of transmembrane G-protein coupled receptors involved in inflammatory responses. FPRs were initially described in immune cells as transducers of chemotactic signals in phagocytes that react to tissue injury. Subsequently, FPRs were also identified in a wide variety of cell types, including cancer cells. Beyond broad cellular distribution, FPRs are also characterized by the ability to bind a variety of ligands with different chemical and biological properties, ranging from natural peptides to synthetic compounds. The binding of FPRs to specific agonists induces a cascade of functional biological events, such as cell proliferation, migration, angiogenesis, and oxidative stress. From all this evidence, it becomes clear that FPRs are multifaceted receptors involved in several pathophysiological processes associated with inflammation. In this review, we provide a comprehensive molecular description of structure-function relationship of FPRs and their pivotal role in the host defense, highlighting the regulatory functions in both the initiation and resolution of inflammation. In addition to their activity as PRRs during innate immune response, we focus on their involvement in pathological conditions, including chronic inflammatory disease, neurodegenerative disorders, and cancer, with special emphasis on FPR targeting as promising therapeutic strategies in the era of precision medicine.